Metallocene polypropylene crystallization kinetic during cooling in rotational molding thermal condition. Issue 1 (14th March 2013) - Sarrabi, Salah; Boyer, S. A. E.; Lacrampe, Marie France; Krawczak, P.; Tcharkhtchi, Abbas
Abstract This article is part of an ambitious project. The aim is to simulate mechanical properties of rotomolded part from microstructure consideration. Main objective here is to consider metallocene polypropylene crystallization kinetic (PP) during cooling stage in rotational molding. Crystallization kinetic of metallocene PP is so rapid that microscopy cannot help to observe nucleation and growth. Crystallization rate can be estimated by a global kinetic. Given that cooling in rotational molding is dynamic with a constant rate, Ozawa law appears more appropriate. Ozawa parameters have been estimated by differential scanning calorimetry. In rotational molding thermal condition, Avrami index identifies a complex nucleation intermediate between spontaneous and sporadic. Ozawa rate constant is 68 times higher than this obtained for Ziegler–Natta PP. By coupling transformation rate from Ozawa model and a thermal model developed earlier, the difference between theory and experimental is less than 1%. To optimize rotational molding, study has been completed by sensitivity to adjustable parameters. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013